A Systematic Review and meta-analysis of the effect of administration of azithromycin during pregnancy on perinatal and neonatal outcomes. (October 2021) - Hume-Nixon, Maeve; Quach, Alicia; Reyburn, Rita; Nguyen, Cattram; Steer, Andrew; Russell, Fiona
Abstract: Background: Currently there are trials in Africa and Asia investigating whether prophylactic azithromycin during pregnancy reduces infection-related neonatal morbidity and mortality. We undertook a systematic review and meta-analysis to determine the effect of azithromycin during pregnancy on perinatal and neonatal outcomes. Methods: We identified articles between January 1990 and 13 th June 2021 by searching five electronic databases. Randomised control trials (RCTs) that included pregnant women administered azithromycin alone or in combination with other medications, and that reported outcomes of low birthweight (LBW), prematurity, stillbirth, and neonatal deaths, infections, and admissions, were eligible. Fixed effects meta-analyses were used for primary analysis. Quality appraisal was performed using Cochrane's Risk of Bias 2 tool. This review was registered with PROSPERO, CRD42019127099. Findings: The search generated 5777 studies, of which 14 studies were included involving 17, 594 participants. Most studies investigated azithromycin as Intermittent Preventive Treatment in Pregnancy (IPTp) for malaria. More than 50% of the studies had low risk of bias for all outcomes, except for LBW and neonatal admissions. Fixed-effects meta-analyses found that azithromycin reduced the risk of LBW (seven studies, Pooled RR 0·79; 95% CI 0·68-0·93; I 2 = 0·00%), and prematurity compared to controls (eight studies, Pooled RR 0·87; 95% CI 0·78-0·98; I 2 = 23·28%). There was no strong evidence of any effect on neonatal mortality, infections and admissions. There was an increase in stillbirth but the 95% CI crossed the null value (seven studies, Pooled RR 1·39; 95% CI 0·94 – 2.07; I 2 =0·00%). However this review was limited by differences in the types of intervention and study populations, and inconsistency in outcome reporting between studies. Interpretation: Prophylactic azithromycin during pregnancy reduces LBW and prematurity. However, as azithromycin has been investigated as part of IPTp, it is unclear whether it would improve perinatal and neonatal outcomes in non-malaria endemic settings. The potential harm on stillbirth rates needs further investigation. Funding: None